Comparison of Image Quality between Swept Source and Spectral Domain OCT in Media Opacification - Maha Asrar, Hina Khan, Bisma Ikram, Muhammad Asif, Aamir Asrar (Pakistan Journal of Ophthalmology, 2016)
Purpose: The study aimed to compare the image quality of SD OCT and SS OCT in the setting of media opacification i.e. cataract. Study Design: Prospective cross sectional study. Place and Duration: Amanat eye hospital from 1st October 2015 till 31st December 2015. Material and Methods: Prospective cross sectional study was carried out on 366 eyes of 241 subjects. All subjects were scanned with both SS – OCT and SD – OCT with dilated pupils and scans were evaluated by two ophthalmologists. Chi square/ fisher exact test was applied to assess the results. Results: In the sample of 366 eyes, there were 174 eyes with grade 1; 96 with grade 2; 72 with grade 3; and 24 with grade 4 cataract media opacification. The images obtained from media opacification grade 1 and 4 were almost constant and statistically non significant. The results of images obtained with grade 2 media opacification was significant with p = 0.001. Similarly, the results obtained from grade 3 media opacification were highly significant with p < 0.001.